(3TQM eNJUQ GdQhVI aj CUhd Gdabgs - (3fLe GdOjf SdjeGf Hf YHO Gdbhi GdWhai GdHZOGOjs; (3YHO Gddg Hf YHO GdQMef GdejbGJj, ehab GdOjf,J (B1223 (3g` s ((3eMeO Hf eMeO Hf eMeO GdMfHdi GdWQGHdSi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe fLe GdOjf SdjeGf Hf YHO Gdbhi GdWhai GdHZOGOi bhdg Gddge jG hGLH GdhLhO hjG ehLO cd ehLhO GdcdGe Ydjg ef hLhg CMOgG Cf gPg GdLedI hfXGFQgG s
(3BNQgG (B:s
(3hGdTjN CHh eMeO ESJhYH GdcdGe Ydjg eY CNhjg ai HGH JbGSje GdCSeGA hgh HGH GddZGJ hai cd NjQ hGddg SHMGfg hJYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HChdgG hBNQgG JedcGJ s
(3HBNQgG bQGAI hebGHdI s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdMfHdjs